2018
DOI: 10.1016/j.eclinm.2018.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent Long-term Transplantation Outcomes for Kidneys Donated After Brain Death and Cardiac Death: Conclusions From a Nationwide Evaluation

Abstract: Background Despite growing waiting lists for renal transplants, hesitations persist with regard to the use of deceased after cardiac death (DCD) renal grafts. We evaluated the outcomes of DCD donations in The Netherlands, the country with the highest proportion of DCD procedures (42.9%) to test whether these hesitations are justified. Methods This study included all procedures with grafts donated after brain death (DBD) (n = 3611) and cardiac death (n = 2711) performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
58
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 29 publications
6
58
1
1
Order By: Relevance
“…Importantly, 10-year transplantation outcomes for the Netherlands are at least equal to countries with younger donors, such as the United States. 37 As expected the majority of þDGF cases were DCD grafts. We noticed similar metabolic profiles for DBD and DCD grafts; however, the power of this explorative study is obviously too low to detect subtle differences between these 2 donor types.…”
Section: Discussionsupporting
confidence: 59%
“…Importantly, 10-year transplantation outcomes for the Netherlands are at least equal to countries with younger donors, such as the United States. 37 As expected the majority of þDGF cases were DCD grafts. We noticed similar metabolic profiles for DBD and DCD grafts; however, the power of this explorative study is obviously too low to detect subtle differences between these 2 donor types.…”
Section: Discussionsupporting
confidence: 59%
“…In addition, no difference in median recipient creatinine at last follow‐up (1.2 mg/dL) was seen between the 2 groups. Previous studies have shown similar longterm outcomes between kidney transplantation alone from DCD and DBD donors . Despite similar longterm outcomes, a higher rate of delayed graft function (DGF) has been well documented when kidney grafts from DCD donors are used compared with those from DBD donors.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have shown similar longterm outcomes between kidney transplantation alone from DCD and DBD donors. (16,17) Despite similar longterm outcomes, a higher rate of delayed graft function (DGF) has been well documented when kidney grafts from DCD donors are used compared with those from DBD donors. The 2 single-center studies investigating DCD-SLKT contained data on post-SLKT DGF.…”
Section: Original Article | 405mentioning
confidence: 99%
“…Optimal induction interventions should be able to repair renal structural damage while inhibiting the immune response (7)(8)(9)(10)(11). There are some studies about DGF, acute rejection, and graft loss in donation after cardiac death and brain death; however, studies on living donation are limited (12)(13)(14). In this study, we focused on the association between DGF and acute rejection in patients who received kidneys from living donors with positive PRA and negative DSA.…”
Section: Introductionmentioning
confidence: 99%